2018
DOI: 10.1080/2162402x.2017.1349588
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating tumor immunity using aptamer-targeted RNAi to render CD8+ T cells resistant to TGFβ inhibition

Abstract: TGFβ secreted by tumor cells and/or tumor infiltrating stromal cells is a key mediator of tumor growth and immune suppression at the tumor site. Nonetheless, clinical trials in cancer patients targeting the TGFβ pathway exhibited at best a modest therapeutic benefit. A likely reason, a common limitation of many cancer drugs, is that the physiologic roles of TGFβ in tissue homeostasis, angiogenesis, and immune regulation precluded the dose escalation necessary to achieve a profound clinical response. Murine stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Recent studies have shown successful delivery of aptamer-conjugated siRNAs (AsiCs) to T lymphocytes in vivo [19,22,[179][180][181][182]. For example, Gilboa et al reported moderate gene silencing levels (30-40%) in CD8 + T lymphocytes using AsiC targeted towards the 4-1BB receptor, a co-stimulatory receptor expressed on activated T cells, to enhance anti-tumor responses in mouse tumor models [179][180][181][182]. Other approaches include the use of CTLA-4 targeting AsiCs to silence STAT3 expression (~75% knockdown) in CTLA4 + T cells to reduce metastasis and tumor growth in various murine tumor models [181].…”
Section: Aptamer-sirna Conjugatesmentioning
confidence: 99%
“…Recent studies have shown successful delivery of aptamer-conjugated siRNAs (AsiCs) to T lymphocytes in vivo [19,22,[179][180][181][182]. For example, Gilboa et al reported moderate gene silencing levels (30-40%) in CD8 + T lymphocytes using AsiC targeted towards the 4-1BB receptor, a co-stimulatory receptor expressed on activated T cells, to enhance anti-tumor responses in mouse tumor models [179][180][181][182]. Other approaches include the use of CTLA-4 targeting AsiCs to silence STAT3 expression (~75% knockdown) in CTLA4 + T cells to reduce metastasis and tumor growth in various murine tumor models [181].…”
Section: Aptamer-sirna Conjugatesmentioning
confidence: 99%
“…4-1BB aptamer has also been used in conjugation with an siRNA against Smad4 in the TGFβ signaling pathway, the signaling of which mediates immune suppression at the tumor microenvironment. The 4-1BB aptamer-Smad4 siRNA conjugates rendered T cell resistant to TGFβ inhibition, and systemic administration of the conjugates to tumor-bearing mice boosted irradiation-and vaccine-induced antitumor immunity [162].…”
Section: Immune Stimulation Agonistsmentioning
confidence: 99%
“…These aptamers were further explored to regulate more benefits. Together with other therapeutic RNAs, several aptamer–siRNA conjugates have been utilized for the in vivo delivery of such cargoes to elicit an antitumor immune response. , Even with the repertoire of such therapeutic ligands, challenges due to spatial and temporal control over delivery, displaying modest clinical response, exist. This obstacle can be overcome by functionalizing it with potential nanocarriers because nanomedicine has escalated the efficiency of cancer immunotherapy.…”
Section: Aptamer–nanocarrier Conjugates For Multifarious Targetingmentioning
confidence: 99%